Pendekatan Partisipatif Dalam Perencanaan Kota: Belajar Dari Den Haag, Belanda - I. Sosrowinarsito; B. Kombaitan (The Institute for Research and Community Services, Institut Teknologi Bandung, 1998)
Public participation has become an important part in development, including urban deve1opnent. This participation is important because development is from the people, by the people and for the people. Only people who know exactly what they want and need. Indonesia already has two general regulations concerning public participation, Law No. 24/1992 on Spatial Planning and Government Regulation No. 6911996 on the Implementation of the Public Rights and Obligation, and the Format and Procedure for Public Participation in Spatial Planning. This article discusses the experience of The Hague, The Netherlands in implementing public participation in urban development through Project The Hague 2025. It is hoped that through the experience of The Hague, Indonesia can learn important lessons for public participation in urban development in Indonesia.